UPAYA PARTAI POLITIK DALAM MEMANFAATKAN DEMOKRASI VIRTUAL DI ERA DIGITAL - Ambia B Boestam; Adi Prakosa; Bhakti Nur Avianto (Jurnal Pustaka Komunikasi, 2023)
The use of public opinion space through the digitalization of virtual democracy has been widely relied on by political parties in conducting political marekting and political communication, especially online-based campaigns. This study aims to find out how political parties' efforts in utilizing virtual democracies in increasing the quantity of potential voters. Descriptive qualitative research method to examine certain events as a new phenomenon in order to answer precisely about the object being observed, assessed and intervened in a complex multi-component using secondary data and literature studies. The results showed that the practices for running a digital democracy are no longer conventional, but through digital media and virtual political spaces. So that digital democracy shows the central position and role of digital parties in Indonesia. The use of virtual democracy provides a strong potential by seeing the large number of people who have begun to participate in online social media, so that virtual democracy feels great benefits as a new channel in the public opinion space to find political news, discuss, organize and to mobilize supporters of one of the political parties it likes